(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The antimicrobial activity of aqueous and organic extracts of the roots and leaves of Senna alata were studied using the cup plate agar diffusion method. All the extracts demonstrated considerable activity against both Gram negative and Gram positive bacteria and some fungi with the organic extracts showing higher activity than the aqueous extracts. The minimum inhibitory concentration and minimum bactericidal concentration of the methanol extracts ranged between 6-20 mg/ml and 25-100 mg/ml for bacteria and fungi respectively. Preliminary phytochemical analysis showed that the extracts contained tannins, saponins, glycosides, flavonoids and phenols. The results obtained show the basis for the local usage of S. alata Linn as an antimicrobial.